2015
DOI: 10.1103/physreva.92.062111
|View full text |Cite
|
Sign up to set email alerts
|

Elementary test for nonclassicality based on measurements of position and momentum

Abstract: We generalise a non-classicality test described by Kot et al. [Phys. Rev. Lett. 108, 233601 (2010)], which can be used to rule out any classical description of a physical system. The test is based on measurements of quadrature operators and works by proving a contradiction with the classical description in terms of a probability distribution in phase space. As opposed to the previous work, we generalise the test to include states without rotational symmetry in phase space. Furthermore, we compare the performa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Experimental measurement of Wigner function negativity requires the development of mechanical state tomography [66]. It may be shown that squeezing a state does not hamper the ability to reconstruct the state Wigner function from measurements of its marginal distributions [67]. As part of this, the quadrature squeezing could also be introduced as simultaneous with the Kerr evolution rather than as a prior step.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental measurement of Wigner function negativity requires the development of mechanical state tomography [66]. It may be shown that squeezing a state does not hamper the ability to reconstruct the state Wigner function from measurements of its marginal distributions [67]. As part of this, the quadrature squeezing could also be introduced as simultaneous with the Kerr evolution rather than as a prior step.…”
Section: Discussionmentioning
confidence: 99%
“…We term this the phase space distribution (PSD) criterion. The PSD criterion has already been experimentally verified for the electromagnetic field associated with a single photon [38], and expanded theoretically to some more general cases [39] in quantum optics.In this Rapid Communication, we apply a modified PSD criterion to the magnetization measurement of the atomic ensemble reported in Ref. [40].…”
mentioning
confidence: 99%
“…We term this the phase space distribution (PSD) criterion. The PSD criterion has already been experimentally verified for the electromagnetic field associated with a single photon [38], and expanded theoretically to some more general cases [39] in quantum optics.…”
mentioning
confidence: 99%